The effect of “annealing” on the specific crushing energy of the layered frozen ice. - V. A. Dzhumandzhi; A. V. Shavlov; I. V. Sokolov; E. S. Yakovenko (Лëд и снег, 2024)
The paper demonstrates realization of an experimental method of shock destruction of ice in order to study its specific energy of destruction and strength under various annealing conditions. Ice was prepared by layer-by layer freezing of distilled water. The ice had a polycrystalline structure with a grain size of several fractions of a millimeter, judging by its ability to be broken into submillimeter fragments under the influence of shock load. It was shown that ice samples can be stored for a long time (several days) at a temperature of –18 °C without changing their physical characteristics. Annealing of ice for more than 5 hours at a temperature of –1.5 °C resulted in a decrease in the diameter of the holes formed on the ice surface by impacts of the ball by 20% and in an increase in the strength of the ice by 80%. Many hours of annealing at a temperature of about 0 °C caused the opposite results: the diameter of the holes increased by 10–20%, and the strength decreased. The increase in ice strength at the annealing temperature of –1.5 °C was explained by a decrease in the specific surface energy of formation of cracks and a decrease in the size of the fragments into which the ice breaks. The decrease in strength at the annealing temperature of 0 °C is explained by ice recrystallization processes, which results in a decrease of the density of microcracks in the ice lattice, and in an increase of the size of fragments. Thus, annealing can significantly affect the strength. To strengthen ice, the annealing temperature must be high, but not too close to the melting point, so that noticeable recrystallization does not occur, leading to a loss of strength of the material.